A Bibliometric Analysis of Internship Research in Indonesia (2015–2025) - Ni made widhi Sugianingsih; Narulita Syarweni; Anwar Mustofa (Merwinspy Publisher, 2026)
Internship programs have emerged as a crucial element of higher education and vocational systems in Indonesia, especially in light of employability needs and legislative changes like Merdeka Belajar–Kampus Merdeka. Despite a rise in research concerning internship-related subjects over the last decade, the literature remains disjointed and lacks a comprehensive review of its evolution and philosophical framework. This study intends to delineate the development, topic concentration, and philosophical underpinnings of internship research in Indonesia from 2015 to 2025 using a bibliometric analysis of Scopus-indexed articles. The research used bibliometric methods using RIS data extracted from the Scopus database to examine publishing trends, prominent authors, journals, and institutions, patterns of keyword co-occurrence, and networks of citations and co-citations. The data indicate a significant rise in internship-related publications from 2015 to 2025, particularly in recent years, reflecting heightened academic interest in internships as employability-focused work-based learning strategies. Thematic analysis reveals three primary clusters: higher education and employability, competence development and individual competitive advantage, and education–industry partnership, in addition to emergent topics including mentality, work happiness, sustainability, and ethics.